Experiences With a Self-Reported Mobile Phone-Based System Among Patients With Colorectal Cancer: A Qualitative Study - Drott, Jenny; Vilhelmsson, Maria; Kjellgren, Karin; Berterö, Carina (JMIR Publications, 2016)
BackgroundIn cancer care, mobile phone-based systems are becoming more widely used in the assessment, monitoring, and management of side effects. ObjectiveTo explore the experiences of patients with colorectal cancer on using a mobile phone-based system for reporting neurotoxic side effects. MethodsEleven patients were interviewed (ages 44-68 years). A semistructured interview guide was used to perform telephone interviews. The interviews were transcribed verbatim and analyzed with qualitative content analysis. ResultsThe patients' experiences of using a mobile phone-based system were identified and constructed as: "being involved," "pacing oneself," and "managing the questions." "Being involved" refers to their individual feelings. Patients were participating in their own care by being observant of the side effects they were experiencing. They were aware that the answers they gave were monitored in real time and taken into account by health care professionals when planning further treatment. "Pacing oneself" describes how the patients can have an impact on the time and place they choose to answer the questions. Answering the questionnaire was easy, and despite the substantial number of questions, it was quickly completed. "Managing the questions" pointed out that the patients needed to be observant because of the construction of the questions. They could not routinely answer all the questions. Patients understood that side effects can vary during the cycles of treatment and need to be assessed repeatedly during treatment. ConclusionsThis mobile phone-based system reinforced the patients' feeling of involvement in their own care. The patients were comfortable with the technology and appreciated that the system was not time consuming.